Continuous descent operations in high throughput and constant wind environment - Low, Yong Lin (2015)
This project report attempted to simulate the flight of a Boeing 747-400 operating under Continuous Descent Operation procedures in an environment with a constant wind velocity. The descent profile was divided into 6 segments each with 2 possible descent modes, namely the Constant Flight Path Angle and Constant Rate of Descent modes, yielding 64 combinations. The 64 combinations were simulated under 2 headwind and 2 tailwind conditions, with speeds of 25 knots and 50 knots. Flight performance calculations were performed at intervals of one second. The simulations showed that a pure constant Flight Path Angle descent was the most fuel efficient, but the introduction of constant rate of descent segments at low altitudes cause only small negative impact on fuel consumption.